Autonomic control of colonic tone and the cold pressore test. - Ford, M J (1996)
BACKGROUND: Cardiovascular responses to cold stimulation are well characterised. It is unclear, however, whether cold pain stimulates responses in colonic tone in the transverse and sigmoid regions. AIMS: To assess the effects of cold stimulation on tone nd motility in the transverse and sigmoid colon and on cardiovascular autonomic activity. METHODS: Phasic and tonic motility of the transverse and sigmoid colon, pulse rate, and beat to beat pulse variability (which are measures of centrally mediated changes in autonomic function) were measured before, during, and after a standard cold pressor test in 22 healthy volunteers. RESULTS: Cold pain induced a significant increase in colonic tone but not phasic contractility in the transverse and sigmoid regions. Simultaneously, cold pain increased pulse interval variability. CONCLUSION: The findings are consistent with the hypotheses that cold pain produces coactivation of both the sympathetic and parasympathetic limbs of the autonomic nervous system and that cold induced changes in colonic tone are temporally associated with alterations in central autonomic nervous activity.